The Complexity of Job Mobility among Young Men - Neal, Derek (Journal of Labor Economics, 1999)
The model of job search involves both employer matches and career matches. Workers may change employers without changing careers but cannot search over possible lines of work while working for one employer. The optimal policy implies a two‐stage search strategy in which workers search over types of work first. The patterns of job changes observed in the National Longitudinal Survey of Youth support this two‐stage search policy. Among male workers who are changing jobs, those who have previously changed employers while working in their current career are much less likely to change careers during the current job change.